2014
DOI: 10.1111/are.12506
|View full text |Cite
|
Sign up to set email alerts
|

Dietary medicinal herbs and enzyme treated fish meal improve stress resistances and growth performance at early juvenile stage of red sea breamPagrus major

Abstract: Red sea bream Pagrus major (RSB) weighing 0.09 g were fed on test diets, composed of 65% fish meal supplemented with 0.49% Crataegi fructus (Cf) and a mixture of Massa medicata, Cf, Artemisia capillaries and Cnidium officinale (HM) or a control diet without herbs, in trial 1. After air exposure and anaesthesia treatment, higher stress tolerances were obtained in herbal groups than control group. Moreover, after challenge test with Vibrio anguillarum, mortalities of the herbal groups were lower than the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
0
6
1
Order By: Relevance
“…Nevertheless, a few studies used herbs in powder form and reported beneficial effects in fish (Reverter et al, 2014; Syahidah et al, 2015). For instance, the supplementation of red sea bream ( Pagrus major ) diet with 0.49% hawthorn powder ( Crataegi fructus ) led to a significant better growth rate than the control (Takaoka et al, 2014). Aside from weight gain and growth, lower carcass saturated fatty acid content was observed in olive flounder ( Paralichthys olivaceus ) following the incorporation of 0.3, 0.5 and 1.0% herbs powder mixture (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, a few studies used herbs in powder form and reported beneficial effects in fish (Reverter et al, 2014; Syahidah et al, 2015). For instance, the supplementation of red sea bream ( Pagrus major ) diet with 0.49% hawthorn powder ( Crataegi fructus ) led to a significant better growth rate than the control (Takaoka et al, 2014). Aside from weight gain and growth, lower carcass saturated fatty acid content was observed in olive flounder ( Paralichthys olivaceus ) following the incorporation of 0.3, 0.5 and 1.0% herbs powder mixture (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, they noted a significant improvement (P<0.05) in feed conversion compared to the control. Contrarily, Kim et al [56] and Takaoka et al [49] observed no significant effects on feed efficiency when utilizing Scutellaria baicalensis Georgi extract or medicinal herbs in catfish (Silurus asotus) or at the early juvenile stage of Red seabream (Pagrus major). FCR: Expressed as g of DM intake / g gain PER:Expressed as g of g gain / g CP intake.…”
Section: Ahmedmentioning
confidence: 99%
“…Maniat et al [48] observed positive growth effects in fish fed phytogenic-enriched diets, such as fenugreek meal, chamomile flowers meal, and garlic, phytogenic-enriched diets, whereas, Takaoka et al [49] found no significant impacts on growth. Additionally, recent research highlights the beneficial effects of LOG juice in other animal species.…”
Section: Growth Performance and Survival Ratio Of Fishmentioning
confidence: 99%
“…In addition, rainbow trout fed diets contained a mixture of thymol and carvacrol improved (P < 0.05) feed efficiency and growth (Giannenas et al., 2012). On the contrary, no impacts of phytobiotics on growth and feed efficiency (Kim et al, 2013;Takaoka et al, 2016). The potential reasons for superiority of the combination phytobiotics than other treatments may be due to the benefit effect of phytobiotics together than when it was used individually.…”
Section: Growth Responses and Feed Efficiency Of Nile Tilapia Fed Expmentioning
confidence: 99%